Effectiveness of Hibiscus sabdariffa Linn for Obesity Treatment: A Systematic Review of Randomized Controlled Trials - Anggraini, Suci; Kartinah, Neng Tine (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Hibiscus sabdariffa Linn. (H. sabdariffa), commonly known as Rosella plants in Indonesia, has had various uses in the food and beverage industry and traditional medicines for hundreds of years. The main compounds of H. sabdariffa have been stated to have anti-obesity effects through its biologically active compounds. This review systematically evaluates the evidence from human randomized clinical trials on the effects of H. sabdariffa extract in obesity, including decreased bodyweight, normalizing the blood lipid profile, and modulating appetite-related biomarkers.Subjects and Method: This review is based on the patient, intervention, comparison, and outcome (PICO) procedure, with the patient is people with obesity, the intervention is the administration of H. sabdariffa extract compared to control that given placebo, and the outcomes are reduced body weight and fat accumulation, normalize blood lipid profiles, and regulate biomarkers related to appetite. Articles used are limited to the publication year between 2013 and 2021. Search is done through PubMed, ScienceDirect, Wiley Online Library, Scopus, and Google Scholar with the keywords “hibiscus sabdariffa and obesity”, “hibiscus sabdariffa and lipogenesis”, “hibiscus sabdariffa and energy metabolism”, and “hibiscus sabdariffa and appetite”.Results: The search resulted in 10 studies involving 453 subjects. We proved several significant effects of H. sabdariffa extract on obese subjects. Administration of H. sabdariffa extract for several doses and several days can improve anthropometry measurement, fat accumulation, increased satiety sensation, while the appetite sensation mainly for fatty, sweet, and salty foods was decreased.Conclusion: This review suggests that the benefit of H. sabdariffa to people with obesity are associated with body weight and blood lipid profile-lowering effect; however, more high-quality clinical trials are needed.Keywords: Hibiscus sabdariffa, obesity, appetiteCorrespondence: Suci Anggraini, Masters Program in Biomedical Science, Faculty of Medicine, Universitas Indonesia. Jl. Salemba Raya 4, Jakarta Pusat, DKI Jakarta 10430. Email: suci.angraini@ui.ac.id . Mobile: 081363397973.Indonesian Journal of Medicine (2021), 06(04): 439-451https://doi.org/10.26911/theijmed.2021.06.04.10